The New Surveillance Normal. - PRICE, DAVID H. (Monthly Review: An Independent Socialist Magazine)
The article discusses purported mass surveillance collaboration between the U.S. National Security Agency (NSA) and corporations. Topics include U.S. public opinion regarding mass surveillance, revelations by former NSA contractor Edward Snowden, and links between the U.S. Central Intelligence Agency (CIA) and corporations. Allegations that the NSA is involved in economic espionage are addressed.